Penerapan Aplikasi Primer 7 untuk Analisis Keanekaragaman dan Penyerapan Karbon oleh Vegetasi Mangrove di Terminal Teluk Lamong - Sophia Alvin Nurina; Yulia Masladen; Tuhu Agung Rachmanto (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Mangrove vegetation plays a crucial role in absorbing carbon dioxide (CO₂) and supporting the sustainability of coastal ecosystems. Terminal Teluk Lamong (TTL), as a strategic port area, has developed mangrove conservation initiatives to support carbon emission mitigation efforts. This study aims to analyze the diversity, biomass, carbon stock, and carbon absorption capacity of mangrove vegetation at TTL using the PRIMER 7 Application. The analysis of mangrove vegetation diversity through PRIMER 7 revealed variations among observation stations at Terminal Teluk Lamong. Station 1 contained four species with a moderate diversity index (H’ = 1.187) and high evenness (J’ = 0.8566). Station 2 had three species with H’ = 0.826, indicating dominance by certain species. Station 3 showed the highest diversity, with six species and H’ = 1.307. Overall, the H’ values ranging from 0.8–1.3 indicate moderate diversity and a relatively stable mangrove community. In addition, the carbon absorption capacity reached 1,875,955.85 kg CO₂/ha, reflecting the high potential of mangrove vegetation in carbon sequestration. The findings highlight the effectiveness of mangroves as a natural carbon sink, which not only contributes to CO₂ absorption but also supports coastal ecosystem stability and environmental sustainability within the port area.